FINANCIAL LITERACY LECTURER IN SOUTH TANGERANG : SOCIOECONOMIC DETERMINANTS AND DEMOGRAPHIC FACTORS - Arianti, Baiq Fitri; Kurnia Shanti, Yunita; Maradina, Julian (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2020)
The purpose of this study is to measure and test the influence of socioeconomic and demographic factors on improving financial literacy in lecturers in South Tangerang City. This type of research uses quantitative research with survey methods. The population is all college lecturers in South Tangerang city asmany as 5,974 respondents andthe sample number of 209 respondents with simple random sampling method. The data sources used are primary and secondary data. The data analysis method used is multiple regression with SPSS version 25. The results found that socioeconomic influence is positive and significant to financial literacy. Variable demographic factors have a positive and significant effect on financial literacy. The results of this study contribute to the field of financial accounting, especially related to socioeconomic factors, demographics and financial literacy that can provide information and input sources for the government, OJKcommunity in helping to improve knowledge and understanding of financial services products as a form of improving financial literacy and needed from various parties especially from the academics of universities who can contribute to the development of theory and study of libraries